The perception of quality and the performance in primary health care of central Alentejo – Portugal - Saraiva, M.; Alfaiate, C.; Gomes, L. P.; Correia, A. R.; Jorge, F. (Cogent Business and Management, 2023)
Quality and performance are current issues and a strategic priority for the Portuguese National Health Service. Currently, there is a lack of studies in primary health care (PHC) that assess the relationship between the quality and the level of performance of the Primary Health Care Teams. In Portugal, those teams are monitored through the Global Performance Index (GPI), which demonstrates, through a score, the procedures and results obtained by electronic records and the metrics defined for each indicator. This paper aims to analyze the relationship between the perception of the quality of health professionals (service culture; leadership; service strategy; infrastructure and external resources; information and knowledge; processes; service management; human resource planning and skills development, commitment; conditions, satisfaction, performance, and recognition; and results) in the different Primary Health Care teams of the PHC of Central Alentejo—Portugal, and the level of performance of the given teams (care performance; professional training; organizational quality; and services). Self-Perception of Quality Questionnaire for Primary Health Care (SPQQ4PHC) was used as an assessment tool. The population comprises 324 health professionals (Family Doctors, Nurses, and Medical Secretaries) distributed over 34 Primary Health Care Teams. When analyzing the global correlation of the variables in the SPQQ4PHC questionnaire with the GPI, it´s possible to confirm that twenty-one out of twenty-five correlates with the GPI. Thus, this study allowed us to conclude that, as health professionals perceive the quality of the variables increases, the GPI also increases, demonstrating that the dimensions of quality and performance are closely related.